Model Pemilihan Pemasok Bahan Baku Kelapa Pada PT.Royal Coconut Di Minahasa Utara Dengan Pendekatan Analytic Hierarchy Process - Gabriela R. Pangemanan; Celsius Talumingan; Olfie Benu; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTThis study aims to analyze the selection of suppliers of coconut raw materials in PT. Royal Coconut with AHP approach (Hirarchy Analytical Process). Data were obtained by interview and questionnaires from the sample determined Judgement sampling and other data obtained from the BPS, the Department of Agriculture and the Department of Trade and Industry, at North Minahasa. Data analysis using AHP approach (Hirarchy Analytical Process)with Expert Choice software 11. The results show that the raw material supplier Area A (region: Maumbi Village, Kawangkoan Village, Village Kolongan, Airmadidi Village, the Village and Village Matungkas Laikit) is a top priority and the second priority area is Area B (region: Tatelu, Talawaan, Airport area) and Area C (Likupang area) and D (region: South Minahasa dan Southeast Minahasa) are the third and forth priority.Methods and Models selection of suppliers of raw materials can be applied by PT. Royal Coconut as reference for decision support system development company. Keyword: PT. Royal Coconut, AHP, Expert Choice, Model Suppliers